1997
DOI: 10.1038/41267
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of activity-dependent synaptic depression in simple neural networks

Abstract: Triple whole-cell recordings from simple networks of cultured hippocampal neurons show that induction of long-term depression at glutamatergic synapses is accompanied by a back propagation of depression to input synapses on the dendrite of the presynaptic neuron. The depression also propagates laterally to divergent outputs of the presynaptic neuron and to convergent inputs on the postsynaptic neuron. There is no forward propagation of depression to the output of the postsynaptic neuron and no presynaptic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(134 citation statements)
references
References 49 publications
8
125
0
1
Order By: Relevance
“…We have shown that the formation of a temporal-feature map with a submillisecond precision can be based on an interplay of local time-resolved Hebbian learning (20,(24)(25)(26)(27)(28)(29)(30)(31)(46)(47)(48)(49) and its propagation along a presynaptic axon (34)(35)(36)(37)(38)(39)50). Our results are in agreement with physiological and anatomical data on the barn owl's laminar nucleus, and they explain the formation of a temporalfeature map.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have shown that the formation of a temporal-feature map with a submillisecond precision can be based on an interplay of local time-resolved Hebbian learning (20,(24)(25)(26)(27)(28)(29)(30)(31)(46)(47)(48)(49) and its propagation along a presynaptic axon (34)(35)(36)(37)(38)(39)50). Our results are in agreement with physiological and anatomical data on the barn owl's laminar nucleus, and they explain the formation of a temporalfeature map.…”
Section: Discussionsupporting
confidence: 86%
“…39). Long-range cytoplasmic signaling within the presynaptic neuron can be responsible for the propagation of both long-term synaptic depression (35)(36)(37) and long-term synaptic potentiation (38). We call this mechanism ''nonspecific axonal learning.''…”
mentioning
confidence: 99%
“…Low-density cultures of rat hippocampal neurons were transfected at 5 days in vitro (DIV5) with plasmids expressing Bcl-x L tagged at the N terminus with green fluorescent protein (GFP-Bcl-x L ) or the Mito-GFP control, in which the mitochondrial targeting sequence of COX4 is fused to GFP. At 12 days posttransfection (DIV17), neurons with green somata were voltage-clamped at their resting potential in the presence of 1 M tetrodotoxin to block action potentials (26), and miniature postsynaptic currents were recorded (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…They were distinguished by the slower decay time of mIPSPs and were sorted on a computer-based template by using pClamp 9.0 (Molecular Devices) according to ref. 26.…”
Section: Methodsmentioning
confidence: 99%
“…In Xenopus nerve-muscle cultures, LTD induced at one neuromuscular synapse can spread to synapses made by the same neuron onto another myocyte, apparently by signaling within the neuronal cytoplasm, because rapid clearance of extracellular fluid does not prevent the spread of depression (135). In networks of cultured hippocampal neurons, LTD and LTP induced at glutamatergic synapses were found to spread retrogradely to the input synapses on the dendrites of the presynaptic neuron (backpropagation), as well as laterally to synapses made by divergent outputs of the presynaptic neuron (presynaptic lateral propagation) (136,137). Although presynaptic lateral propagation may be accounted for by the possibility of local spread of a diffusible retrograde signal between postsyn-aptic spines of different neurons sharing the same presynaptic bouton (''multisynapse'' bouton; see ref.…”
Section: Retrograde Signaling During Synaptogenesismentioning
confidence: 99%